2020
DOI: 10.1186/s13033-020-00415-1
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness for psychosis groups; description and preliminary evaluation of a novel routine care pathway in Hong Kong

Abstract: Background There is no current guidance on where Mindfulness for Psychosis groups should best be situated within care pathways. The objectives of this paper are to (1) describe a novel care pathway tested out in a psychiatric outpatient service in Hong Kong, and (2) to present feasibility outcomes on attendance and drop-out, and routine clinical outcomes. Methods A new mindfulness pathway was set up, for service users with psychosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…We then moved on to reviewing the data extracted from the remaining mixed-methods studies, to build on our initial synthesis of findings. We found that the majority of mixed-methods studies yielded limited qualitative data from feedback forms or brief interviews, and did not report any findings specifically about home practice [ 20 , 21 , 23 26 , 36 38 ]. The one exception to this was the study by Tong et al [ 27 ], who conducted a full grounded theory analysis of the experience of 11 group participants.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We then moved on to reviewing the data extracted from the remaining mixed-methods studies, to build on our initial synthesis of findings. We found that the majority of mixed-methods studies yielded limited qualitative data from feedback forms or brief interviews, and did not report any findings specifically about home practice [ 20 , 21 , 23 26 , 36 38 ]. The one exception to this was the study by Tong et al [ 27 ], who conducted a full grounded theory analysis of the experience of 11 group participants.…”
Section: Resultsmentioning
confidence: 98%
“…RCT 50 39. Ting et al [ 36 ] Pre-post study Hong Kong Outpatients Mindfulness for Psychosis, n = 22 None 1 × 75 min session/week for 4 weeks Feasibility and acceptability 4. Quantitative Descriptive 100 40.…”
Section: Resultsmentioning
confidence: 99%
“…Studies revealed that females were more likely than males to engage in mindfulness or meditation interventions (Bodenlos et al, 2017; Upchurch & Johnson, 2019). Further, participants in MBIs studies conducted in the Hong Kong community mental health settings were predominately female (Lam et al, 2020; Ting et al, 2020). Further research can explore such gender disparity among MBIs.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, varios estudios han reportado resultados prometedores sobre el deterioro cognitivo y la sintomatología negativa residual en personas con esquizofrenia (Ting et al, 2020;Shen et al, 2023), promoviendo la recuperación a través de un mejor funcionamiento diario (Ting et al, 2020) y la calidad de vida (López-Navarro et al, 2015). Además, la integración de la atención plena a un programa de rehabilitación cognitiva en psicosis ha demostrado efectos positivos sobre el control inhibitorio (López-Navarro et al, 2020), estrechamente relacionado con la calidad de vida y el funcionamiento social en psicosis (Ojeda et al, 2019;Peña et al, 2018).…”
Section: Introductionunclassified